2009
DOI: 10.1159/000215580
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Carcinoembryonic Antigen-Related Cell Adhesion Molecule 1 in Oral Squamous Cell Carcinoma: Correlation with Tumor Progression and Poor Prognosis

Abstract: Objective: To identify genes associated with therapeutic targets of oral squamous cell carcinoma (OSCC), we compared gene expression profiles in OSCC-derived cell lines with human normal oral keratinocytes. Methods: We analyzed the gene expression profiles of OSCCs using Affymetrix GeneChip analysis. The identified genes were analyzed by an Ingenuity Pathway Analysis tool to identify networks of interacting genes. A candidate gene was further evaluated for the expression status of the mRNA and protein in OSCC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…A tendency for decreased expression of ADAM33 mRNA in OSCC cell lines was also shown. These results were consistent with the data found in our previous DNA microarray analysis (13,16). Since mRNA expressions of other members of the ADAM family varied in OSCC cell lines examined, definitive conclusions could not be obtained.…”
Section: Mrna Expression Analysissupporting
confidence: 88%
See 2 more Smart Citations
“…A tendency for decreased expression of ADAM33 mRNA in OSCC cell lines was also shown. These results were consistent with the data found in our previous DNA microarray analysis (13,16). Since mRNA expressions of other members of the ADAM family varied in OSCC cell lines examined, definitive conclusions could not be obtained.…”
Section: Mrna Expression Analysissupporting
confidence: 88%
“…We examined the mRNA expression levels of the six ADAM genes (ADAM9, ADAM10, ADAM12, ADAM17, ADAM28 and ADAM33) that showed significance in DNA microarray analysis performed previously (13,16). The present study revealed higher expression of ADAM12 mRNA in all OSCC cell lines examined when compared with HNOKs (Fig.…”
Section: Mrna Expression Analysismentioning
confidence: 57%
See 1 more Smart Citation
“…The results of microarray analysis provide researchers with high throughput screening to study the roles played by specific genes in cancer development and progression. We previously reported gene expression profiling of OSCC to identify cancer-related genes (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics and functions of CEACAM1 have been demonstrated in individual reports. CEACAM1 is frequently downregulated or dysregulated in multiple human tumors, [22][23][24][25] and is capable of suppressing cell growth and inducing apoptosis. [26][27][28] Ebrahimnejad et al demonstrated that exogenous expression of CEACAM1 enhances melanoma cell invasion and migration; and this enhanced motility can be reverted by anti-CEACAM antibodies.…”
mentioning
confidence: 99%